Statement made by Jane Tolmach to the Chairman of Camarillo and Oxnard Airport Authorities May, 1999 - Jane Tolmach:::::: (1999)
A statement made by Jane Tolmach requesting that the Master Plan, the Environmental Impact Report, and the Noise Study be brought back to the Committees with the request that they mitigate noise problems in residential areas.